Analytical methods for internal pores in powder particles

By mixing powder particles with embedding agent to prepare cured samples, and using argon ion polishing and scanning electron microscopy technology, the problems of limited field of view of internal hole detection of powder particles and difficulty in sample preparation in the prior art are solved, and the powder particles are achieved Accurate quantitative analysis of internal holes.

CN114839211BActive Publication Date: 2025-02-07CHINA NAT PETROLEUM CORP +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110144435.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-02-02
Publication Date
2025-02-07
Estimated Expiration
2041-02-02

AI Technical Summary

Technical Problem

When detecting internal holes of powder particles with particle sizes of 2μm-10μm, the optical microscope has limited field of vision and difficult statistics, high requirements for preparation of scanning electron microscope samples, and it is easy to have oxidative damage layers, and it is impossible to accurately evaluate the pore rate.

Method used

The cured sample is prepared by mixing the powder to be tested with the embedded agent, and the observation surface is polished by argon ion, and multiple images are captured and analyzed by scanning electron microscope to obtain parameters related to the properties of the holes to realize quantitative analysis of the holes inside the powder particles. .

Benefits of technology

Accurately reducing the true structure inside the powder particles, it can complete the precise quantification analysis of the pores inside the powder particles, and is suitable for powder particles with particle sizes of 2μm-10μm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114839211B_ABST
    Figure CN114839211B_ABST
Patent Text Reader

Abstract

The invention discloses an analysis method for internal pores of powder particles, belonging to the field of analysis technology. The analysis method comprises: mixing the powder to be tested and the embedding agent to prepare a solidified sample; determining the observation surface of the solidified sample, and performing argon ion polishing on the observation surface; observing the observation surface after argon ion polishing with a scanning electron microscope, randomly photographing the observation surface under a set field of view, and obtaining multiple scanning electron microscope images; analyzing the multiple scanning electron microscope images, obtaining parameters related to the properties of the pores, and realizing the analysis of the internal pores of the powder particles; the above parameters include the total number of powder particles in multiple scanning electron microscope images, the total number of pores in multiple scanning electron microscope images, the sum of all pore diameters, the average diameter of the pores, the total number of particles with pores in multiple scanning electron microscope images, the sum of all particle diameters with pores, and the average diameter of particles with pores. The method is suitable for quantitative and qualitative analysis of internal pores of powder particles with a particle size of 2μm-10μm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of analytical technology, and in particular to an analytical method for internal pores of powder particles. Background Art

[0002] Metal powder is usually prepared by atomization, also known as spraying. During the preparation process, when the atomizing gas enters the droplets, due to the fast solidification speed, the atomizing gas has no time to be discharged from the metal powder particles, resulting in defects such as cavities inside the metal powder particles. After these defective metal powder particles are made into products through the powder metallurgy process, pores will be generated inside the product, forming a fracture source. It can be seen that the presence of pores in the metal powder will cause cavities in the metal dense material prepared from the metal powder. The presence of a large number of pores in the metal powder will lead to a decrease in the tensile strength and yield strength of the metal dense material, especially a significant deterioration in fatigue performance.

[0003] Powder porosity is a key indicator for evaluating the performance of metal powders. Currently, the powder interior is generally inspected using a scanning electron microscope after polishing the powder mount or an optical microscope.

[0004] In the process of implementing the present invention, the inventors found that there are at least the following problems in the prior art:

[0005] When using an optical microscope to observe powder particles with a particle size of 2μm-10μm, the field of view magnification is limited and statistics are difficult. When using a scanning electron microscope for observation, the sample preparation requirements are very high. The use of mounted samples and polishing treatments can easily lead to the formation of an oxidation damage layer, making it impossible to restore the true internal structure of the powder particles, and thus unable to accurately evaluate the internal porosity of the particles. Summary of the invention

[0006] In view of this, the present invention provides a method for analyzing the internal pores of powder particles, which can solve the above technical problems.

[0007] Specifically, the following technical solutions are included:

[0008] A method for analyzing pores inside powder particles, the method comprising:

[0009] The powder to be tested and the embedding agent are mixed to prepare a solidified sample;

[0010] determining an observation surface of the cured sample, and performing argon ion polishing on the observation surface;

[0011] Observe the observation surface after argon ion polishing by using a scanning electron microscope, randomly photograph the observation surface under a set field of view, and obtain multiple scanning electron microscope images;

[0012] Analyzing the plurality of scanning electron microscope images to obtain parameters related to pore properties, and analyzing the pores inside the powder particles according to the parameters related to the pore properties;

[0013] Among them, the parameters related to the properties of the pores include: the total number of powder particles in the multiple scanning electron microscope images, the total number of pores in the multiple scanning electron microscope images, the sum of all pore diameters, the average diameter of the pores, the total number of particles with pores in the multiple scanning electron microscope images, the sum of all particle diameters with pores, and the average diameter of particles with pores.

[0014] In some possible implementations, the method further includes: obtaining a void coefficient and a void ratio by using the parameters related to the void properties.

[0015] In some possible implementations, the step of mixing the powder to be tested and the embedding agent to prepare a solidified sample comprises:

[0016] The embedding agent and the powder to be tested are mixed evenly on a glass slide at a mass ratio of 2-3:1 to obtain a mixture;

[0017] Performing molding treatment on the mixture to obtain a block sample;

[0018] The block sample is subjected to a thermal curing treatment to obtain the cured sample.

[0019] In some possible implementations, the embedding agent includes: epoxy resin and epoxy resin curing agent in a mass ratio of 5-10:1.

[0020] In some possible implementations, the supporting surface of the glass slide has a non-stick layer.

[0021] In some possible implementations, the molding the mixture to obtain a block sample includes:

[0022] Placing the mixture in a forming mold with a groove cavity and pressing it to obtain the block sample;

[0023] Wherein, the inner wall of the groove cavity is configured to have an anti-sticking function for the mixture.

[0024] In some possible implementations, the block sample is a rectangular block.

[0025] In some possible implementations, the heat-curing the block sample to obtain the cured sample includes: curing the block sample at a temperature of 120° C.-140° C. for 15 min-30 min to obtain the cured sample.

[0026] In some possible implementations, the observation surface is subjected to argon ion polishing by an argon ion cross-section polisher;

[0027] The working parameters of the argon ion cross-section polisher are as follows:

[0028] The acceleration voltage is 4V-6V;

[0029] The ion beam diameter is 500μm-700μm;

[0030] The rotation angle of the cured sample was ±5°.

[0031] In some possible implementations, the particle size of the powder is in the range of 2 μm-10 μm.

[0032] The beneficial effects of the technical solution provided by the embodiment of the present invention include at least:

[0033] The method for analyzing the internal pores of powder particles provided by the embodiment of the present invention is to perform argon ion polishing on the observation surface of the solidified sample prepared by the powder to be tested and the embedding agent, so that the polished observation surface is free of any damage, which is conducive to accurately restoring the real structure inside the powder particles. The observation surface after argon ion polishing is photographed by a scanning electron microscope, and multiple scanning electron microscope images are obtained for each observation surface. Then, by analyzing all the scanning electron microscope images, it is not only possible to complete the qualitative analysis of the internal pores of the powder particles, but also to obtain parameters related to the properties of the pores. The parameters related to the properties of the pores can be used to complete the quantitative analysis of the internal pores of the powder particles. Among them, the parameters related to the properties of the pores include: the total number of powder particles in multiple scanning electron microscope images, the total number of pores in multiple scanning electron microscope images, the average diameter of the pores, the sum of the diameters of all pores, the average diameter of the powder particles, and the sum of the diameters of all powder particles. Based on the above parameters, the properties of the internal pores of the powder particles can be accurately evaluated, and the accurate quantitative analysis of the internal pores of the powder particles can be completed.

[0034] In particular, the method for analyzing the internal pores of powder particles provided by the embodiment of the present invention is suitable for accurate quantitative and qualitative analysis of the internal pores of powder particles with a particle size of 2 μm-10 μm. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0036] Figure 1This is an exemplary scanning electron microscope image provided in Example 1 of the present invention. The scanning electron microscope image is obtained at a field of view of 3000 times. DETAILED DESCRIPTION

[0037] To make the technical solutions and advantages of the present invention more clear, the embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0038] Metal powder is usually prepared by atomization, also known as spraying. During the preparation process, when the atomizing gas enters the droplets, due to the fast solidification speed, the atomizing gas has no time to be discharged from the metal powder particles, resulting in defects such as cavities inside the metal powder particles. After these defective metal powder particles are made into products through the powder metallurgy process, pores will be generated inside the product, forming a fracture source. It can be seen that the presence of pores in the metal powder will cause cavities in the metal dense material prepared from the metal powder. The presence of a large number of pores in the metal powder will lead to a decrease in the tensile strength and yield strength of the metal dense material, especially a significant deterioration in fatigue performance.

[0039] Powder porosity is a key indicator for evaluating the performance of metal powders. Currently, the powder interior is generally inspected using a scanning electron microscope after polishing the powder mount or an optical microscope.

[0040] However, when using an optical microscope to observe powder particles with a particle size of 2μm-10μm, the field of view magnification is limited and statistics are difficult. When using a scanning electron microscope for observation, the sample preparation requirements are very high. The use of mounted samples and polishing treatments can easily lead to the formation of an oxidation damage layer, making it impossible to restore the true internal structure of the powder particles, and thus unable to accurately evaluate the internal porosity of the particles.

[0041] In addition, the currently available statistical methods can only perform qualitative analysis of the pores inside the powder, but cannot perform accurate quantitative analysis.

[0042] An embodiment of the present invention provides a method for analyzing pores inside powder particles, and the method for analyzing pores inside powder particles comprises the following steps:

[0043] Step 1: Mix the powder to be tested and the embedding agent to prepare a solidified sample.

[0044] Step 2: Determine the observation surface of the cured sample and perform argon ion polishing on the observation surface.

[0045] Step 3: Use a scanning electron microscope to observe the observation surface after argon ion polishing, randomly photograph the observation surface under a set field of view, and obtain multiple scanning electron microscope images.

[0046] Step 4: Analyze multiple scanning electron microscope images to obtain parameters related to pore properties, and analyze the pores inside the powder particles based on the parameters related to the pore properties.

[0047] Among them, the parameters related to the properties of pores include: the total number of powder particles in multiple scanning electron microscope images, the total number of pores in multiple scanning electron microscope images, the sum of all pore diameters, the average diameter of the pores, the total number of particles with pores in multiple scanning electron microscope images, the sum of all particle diameters with pores, and the average diameter of particles with pores.

[0048] The method for analyzing the internal pores of powder particles provided by the embodiment of the present invention is to perform argon ion polishing on the observation surface of the solidified sample prepared by the powder to be tested and the embedding agent, so that the polished observation surface is free of any damage, which is conducive to accurately restoring the real structure inside the powder particles. The observation surface after argon ion polishing is photographed by a scanning electron microscope, and multiple scanning electron microscope images are obtained for each observation surface. Then, by analyzing all the scanning electron microscope images, it is not only possible to complete the qualitative analysis of the internal pores of the powder particles, but also to obtain parameters related to the properties of the pores. The parameters related to the properties of the pores can be used to complete the quantitative analysis of the internal pores of the powder particles. Among them, the parameters related to the properties of the pores include: the total number of powder particles in multiple scanning electron microscope images, the total number of pores in multiple scanning electron microscope images, the sum of all pore diameters, the average diameter of the pores, the total number of particles with pores in multiple scanning electron microscope images, the sum of all particle diameters with pores, and the average diameter of particles with pores. Based on the above parameters, the properties of the internal pores of the powder particles can be accurately evaluated, and the accurate quantitative analysis of the internal pores of the powder particles can be completed.

[0049] In particular, the method for analyzing the internal pores of powder particles provided by the embodiment of the present invention is suitable for accurate quantitative and qualitative analysis of the internal pores of powder particles with a particle size of 2 μm-10 μm.

[0050] It should be noted that, in the embodiment of the present invention, the cross section of each hole / powder particle is regarded as a circular structure, and the maximum size of the cross section of the hole / powder particle is regarded as the diameter of the hole / powder particle.

[0051] The total number of powder particles in multiple SEM images refers to: the total number of powder particles contained in all SEM images;

[0052] The statistics of the total number of powder particles in the embodiment of the present invention at least comply with the following rules:

[0053] (1) The number of powder particles with bright white surface in the SEM image;

[0054] (2) Particles with a cross-sectional size of less than 2 μm are not counted;

[0055] (3) Particles located at the edge of the photo that cannot be fully displayed are not counted.

[0056] The total number of holes in multiple SEM images refers to: the total number of holes included in all SEM images;

[0057] The total number of particles with holes in multiple SEM images refers to: the total number of particles with holes included in all SEM images;

[0058] The sum of all hole diameters refers to: the sum of the diameters of all holes included in the SEM images;

[0059] The average diameter of the holes refers to: the sum of all hole diameters divided by the total number of holes in multiple SEM images;

[0060] The sum of the diameters of all particles with pores refers to: the sum of the diameters of the particles with pores included in all scanning electron microscope images; the average diameter.

[0061] The average diameter of the particles with holes refers to: the sum of the diameters of all the particles with holes divided by the total number of particles with holes in multiple scanning electron microscope images.

[0062] Furthermore, the analysis method provided by the embodiment of the present invention also includes: using the above parameters related to the pore properties to obtain the pore coefficient and the pore ratio.

[0063] Specifically, the void coefficient=(the sum of all void diameters÷the sum of diameters of all particles having voids)*1000.

[0064] Porosity = (total number of particles with pores / total number of powder particles) * 100%. The porosity can reflect the proportion of particles with pores in the powder particles.

[0065] By using the above-mentioned porosity coefficient and porosity ratio, the distribution of pores inside the powder can be quantitatively analyzed more intuitively.

[0066] The following is a further detailed description of each step of the method for analyzing the internal pores of powder particles involved in the embodiment of the present invention:

[0067] For step 1, the powder to be tested and the embedding agent are mixed to prepare a solidified sample, which includes the following steps:

[0068] Step 101: Evenly mix the embedding agent and the powder to be tested on a glass slide at a mass ratio of 2-3:1 to obtain a mixture.

[0069] For example, the embedding agent used includes, but is not limited to, epoxy resin and epoxy resin curing agent in a mass ratio of 5-10:1. This type of embedding agent can make the powder to be tested dispersed evenly and stably therein, thereby achieving the purpose of fixation.

[0070] In addition, in order to prevent the powder particles to be tested from adhering to the carrying surface of the glass slide and facilitate molding and removal, the carrying surface of the glass slide is provided with an anti-sticking layer in the embodiment of the present invention. For example, the anti-sticking layer can be made of polytetrafluoroethylene, such as polytetrafluoroethylene tape.

[0071] Step 102, shaping the mixture to obtain a block sample.

[0072] For example, step 102 includes: placing the mixture in a molding die having a groove cavity, and pressing and molding the mixture to obtain a block sample; wherein the inner wall of the groove cavity is configured to have an anti-sticking function for the mixture.

[0073] For example, a molding die whose entire material is polytetrafluoroethylene can be used, or a polytetrafluoroethylene coating can be applied only on the inner wall of the groove cavity of the molding die to achieve the anti-sticking function.

[0074] The structure of the block sample in the embodiment of the present invention includes but is not limited to: a rectangular block, a pentahedral block, a hexahedral block or a disc.

[0075] In order to facilitate the forming process of the block sample and obtain a sufficiently large observation surface, the block sample is made into a rectangular block structure.

[0076] Step 103, performing thermal curing treatment on the block sample to obtain a cured sample.

[0077] For example, step 103 includes: curing the block sample at a temperature of 120° C. to 140° C. for 15 min to 30 min to obtain a cured sample.

[0078] For example, the thermal curing temperature includes but is not limited to: 120° C., 125° C., 130° C., 135° C., 140° C., etc.

[0079] The thermal curing treatment time includes but is not limited to: 15min, 18min, 20min, 22min, 25min, 28min, 30min, etc.

[0080] For step 2, the observation surface of the solidified sample is determined, and the observation surface is subjected to argon ion polishing. Before the observation surface is subjected to argon ion polishing, a pre-polishing treatment can be performed by conventional mechanical polishing means to improve the polishing effect and efficiency of the argon ion polishing treatment.

[0081] Among them, one surface of the fixed sample can be used as the observation surface, and two surfaces of the fixed sample can also be used as the observation surface.

[0082] In the embodiment of the present invention, the observation surface is subjected to argon ion polishing by an argon ion cross-section polisher. The embodiment of the present invention uses argon ion polishing technology to polish the observation surface of the fixed sample to remove the damaged layer, thereby obtaining a high-quality fixed sample that restores the real structure inside the material. According to the physical properties of the fixed sample, the corresponding voltage, current, angle of the ion gun, and ion beam diameter can be adaptively set to control the depth, intensity, and angle of the argon ion action.

[0083] In order to obtain a better polishing effect, as an example, the working parameters of the argon ion cross-section polisher are as follows:

[0084] The acceleration voltage is 4V-6V, for example, 5V;

[0085] The ion beam diameter is 500 μm-700 μm, for example 600 μm;

[0086] The rotation angle of the cured specimen was ±5°.

[0087] Under the above working parameters, the observation surface of the prepared fixed sample is not only smooth and undamaged, but also the tiny pores inside the powder particles can be clearly observed when magnified to 10K times under a scanning electron microscope, and the boundaries of different material layers inside the material can be seen clearly, which is conducive to obtaining more accurate analysis results.

[0088] For step 3, a scanning electron microscope is used to observe the observation surface after argon ion polishing, and the observation surface is randomly photographed under a set field of view to obtain multiple scanning electron microscope images.

[0089] Using a scanning electron microscope to observe the observation surface after argon ion polishing is conducive to the accurate evaluation of the internal pores of powder particles, especially ultrafine powder particles.

[0090] For example, the observation surface is randomly photographed at a field of view of 3000 times, that is, photographed from multiple angles to capture all powder particles as comprehensively as possible.

[0091] Step 4, analyzing the multiple scanning electron microscope images to obtain parameters related to the properties of the pores, and analyzing the pores inside the powder particles based on the parameters related to the properties of the pores.

[0092] Among them, the parameters related to the properties of pores include: the total number of powder particles in multiple scanning electron microscope images, the total number of pores in multiple scanning electron microscope images, the sum of all pore diameters, the average diameter of the pores, the total number of particles with pores in multiple scanning electron microscope images, the sum of all particle diameters with pores, and the average diameter of particles with pores.

[0093] For example, in an embodiment of the present invention, the image processing software imageJ can be used to analyze the scanning electron microscope image, obtain parameters related to the pore properties, and realize quantitative analysis of the pore evaluation of the powder particles.

[0094] The method for analyzing the internal pores of powder particles provided in the embodiment of the present invention is particularly suitable for analyzing and evaluating the internal pores of ultrafine powder particles. For example, the particle size range of the ultrafine powder particles is 2 μm-10 μm.

[0095] The powders involved in the method for analyzing the internal pores of powder particles provided in the embodiments of the present invention include but are not limited to the following:

[0096] (1) Metal powders such as lead, tin, aluminum, copper, nickel, and iron produced by atomization;

[0097] (2) It can also be alloy powder used to prepare bronze, brass, carbon steel, alloy steel, etc.

[0098] (3) Non-metallic powder particles such as ceramics and polymers.

[0099] In summary, the method for analyzing the internal pores of powder particles provided by the embodiment of the present invention has at least the following advantages:

[0100] (1) The embodiments of the present invention provide a method for evaluating the internal pores of ultrafine powder particles with a particle size of 2 μm-10 μm in the field of powder detection.

[0101] Argon ion polishing technology is used in the sample preparation process, which can remove the gas in the solid sample through the vacuum method, and polish the sample surface with argon ion polishing technology to remove the damaged layer, thereby obtaining a high-quality sample that restores the true structure inside the material, solving the problem of sample oxidation damage caused by traditional sample preparation methods.

[0102] The observation surface of the prepared solid sample is not only smooth and undamaged, but the tiny pores inside the powder particles can be clearly observed when magnified to 10K times under SEM, and the boundaries between different material layers inside the material can be clearly seen, which solves the problem of blurred interface and inability to accurately evaluate defects caused by quality problems in sample observation surface preparation in traditional methods.

[0103] The image processing software imageJ was used to analyze the scanning electron microscope images, obtain parameters related to the pore properties, and realize quantitative analysis of the pore evaluation of powder particles.

[0104] The powders involved in the method for analyzing the internal pores of powder particles provided in the embodiments of the present invention include but are not limited to the following:

[0105] (1) Metal powders such as lead, tin, aluminum, copper, nickel, and iron produced by atomization;

[0106] (2) It can also be alloy powder used to prepare bronze, brass, carbon steel, alloy steel, etc.

[0107] (3) Non-metallic powder particles such as ceramics and polymers.

[0108] The present invention will be further described below by way of specific examples:

[0109] Example 1

[0110] This embodiment 1 provides a method for analyzing pores inside powder particles, comprising the following steps:

[0111] Step 11: Mix the embedding agent and the powder to be tested evenly on a glass slide at a mass ratio of 2:1 to obtain a mixture.

[0112] The embedding agent is epoxy resin and epoxy resin curing agent in a mass ratio of 7:1. A polytetrafluoroethylene tape layer is provided on the supporting surface of the glass slide.

[0113] Step 12: Place the mixture in a molding mold with a groove cavity and press-form it to obtain a rectangular block sample with a size of 8 mm*8 mm*3 mm, and a polytetrafluoroethylene tape layer is provided on the inner wall of the groove cavity.

[0114] Step 13: The block sample is heat-cured at 130° C. for 20 minutes to obtain a cured sample.

[0115] Step 14: Determine the observation surface of the cured sample, pre-polish the observation surface by conventional mechanical polishing means, and then perform argon ion polishing on the observation surface by an argon ion cross-section polisher.

[0116] The working parameters of the argon ion cross-section polisher are as follows: the acceleration voltage is 5 V; the ion beam diameter is 600 μm; and the rotation angle of the solidified sample is ±5°.

[0117] Step 15: Use a scanning electron microscope to observe the observation surface after argon ion polishing, randomly photograph the observation surface at a field of view of 3000 times, and obtain 10 scanning electron microscope images. Among them, Figure 1 One of the scanning electron microscope images is shown below.

[0118] Step 16: Use image processing software imageJ to analyze 10 scanning electron microscope images of each observation surface to obtain parameters related to the properties of the pores, and based on the parameters related to the properties of the pores, analyze the pores inside the powder particles.

[0119] Among them, the parameters related to the properties of pores include: the total number of powder particles in multiple scanning electron microscope images, the total number of pores in multiple scanning electron microscope images, the sum of all pore diameters, the average diameter of pores, the total number of particles with pores in multiple scanning electron microscope images, the sum of all particle diameters with pores, the average diameter of particles with pores, the pore coefficient and the pore ratio.

[0120] After analysis, in this embodiment 1, after using imageJ software to count 10 scanning electron microscope images, the parameters related to the properties of the holes are specifically as follows:

[0121] (1) The total number of powder particles is 2104, the total number of particles with holes is 59, and the total number of holes is 61;

[0122] (2) The average diameter of the pores is 0.383 μm, and the sum of all pore diameters is 23.337 μm;

[0123] (3) The average diameter of particles with holes is 3.616 μm, and the total diameter of all particles with holes is 213.358 μm;

[0124] (4) According to calculation, the void coefficient is 110 and the void ratio is 3%.

[0125] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of the present invention and is not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for analyzing the internal pores of powder particles, characterized in that: The method for analyzing the internal pores of the powder particles comprises: The embedding agent and the powder to be tested are mixed uniformly on a glass slide at a mass ratio of 2-3:1 to obtain a mixture; the supporting surface of the glass slide has an anti-sticking layer; the particle size of the powder ranges from 2 μm to 10 μm; The mixture is placed in a forming mold with a groove cavity, and pressed to obtain a block sample; Wherein, the inner wall of the groove cavity is configured to have an anti-sticking function for the mixture; The block sample is subjected to thermal curing treatment to obtain a cured sample; the observation surface of the cured sample is determined, and after pre-polishing treatment by mechanical polishing means, the observation surface is subjected to argon ion polishing treatment by an argon ion cross-section polisher; wherein the working parameters of the argon ion cross-section polisher are as follows: the acceleration voltage is 4V-6V; the ion beam diameter is 500μm-700μm; the rotation angle of the cured sample is ±5°; Observe the observation surface after argon ion polishing by using a scanning electron microscope, and randomly photograph the observation surface from multiple angles under a set field of view to obtain multiple scanning electron microscope images; Analyzing the plurality of scanning electron microscope images to obtain parameters related to pore properties, and analyzing the pores inside the powder particles according to the parameters related to the pore properties; Among them, the parameters related to the properties of the pores include: the total number of powder particles in the multiple scanning electron microscope images, the total number of pores in the multiple scanning electron microscope images, the sum of all pore diameters, the average diameter of the pores, the total number of particles with pores in the multiple scanning electron microscope images, the sum of all particle diameters with pores, and the average diameter of particles with pores.

2. The method for analyzing the internal pores of powder particles according to claim 1, characterized in that: The method further includes: obtaining a void coefficient and a void ratio by using the parameters related to the void properties.

3. The method for analyzing the internal pores of powder particles according to claim 1, characterized in that: The embedding agent comprises: epoxy resin and epoxy resin curing agent in a mass ratio of 5-10:

1.

4. The method for analyzing pores inside powder particles according to claim 1, characterized in that: The block sample is a rectangular block.

5. The method for analyzing internal pores of powder particles according to claim 1, characterized in that: The step of subjecting the block sample to thermal curing to obtain a cured sample comprises: subjecting the block sample to thermal curing for 15 min-30 min at a temperature of 120° C.-140° C. to obtain the cured sample.

Citation Information

Patent Citations

  • Preparation method of scanning electron microscope section sample of micron-sized powder

    CN111982948A